2003
DOI: 10.1177/0020872803046002002
|View full text |Cite
|
Sign up to set email alerts
|

International Social and Economic Justice and On-line Advocacy

Abstract: Social work is unusual among the professions for its commitment to advocacy on behalf of the poor, the dispossessed and the disadvantaged. International human rights and the promotion of social and economic justice are clearly a part of this mission. The article addresses an emerging aspect of advocacy by examining the nexus between international social and economic justice issues and the social work response. It addresses the revolution in advocacy methods created by information technology. These new techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Advocacy-whether directly through lobbying or indirectly through grassroots mobilization, coalition building, or public education-is a core function of nonprofit organizations, for it is through such efforts that organizations can further represent the interests of their constituents (Guo & Saxton, 2010;Mosley, 2013). Social work in particular has a strong professional commitment to social justice and advocacy (Queiro-Tajalli, Campbell, & McNutt, 2003). Not surprisingly, a large body of research has shown how new media are changing the nature of advocacy work.…”
Section: Prior Researchmentioning
confidence: 99%
“…Advocacy-whether directly through lobbying or indirectly through grassroots mobilization, coalition building, or public education-is a core function of nonprofit organizations, for it is through such efforts that organizations can further represent the interests of their constituents (Guo & Saxton, 2010;Mosley, 2013). Social work in particular has a strong professional commitment to social justice and advocacy (Queiro-Tajalli, Campbell, & McNutt, 2003). Not surprisingly, a large body of research has shown how new media are changing the nature of advocacy work.…”
Section: Prior Researchmentioning
confidence: 99%
“…It has been argued that social workers must be advocates for a just world (Queiro-Tajalli et al, 2003) and that social justice is the organizing principle of social work (Brocato and Wagner, 2003). In fact, the Council on Social Work Education (CSWE) has mandated that social justice be a prominent part of the social work curriculum (CSWE, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social work literature on integrating technology into practice and social work curriculum is on the rise (Belluomini 2017 ; Perron et al 2010 ; Cosner Berzin et al 2015 ; Allen et al 2010 ; Stuhlmiller and Tolchard 2009 ; VanDeMark et al 2010 ; Youn 2007 ). However, there is relatively little social work literature on the topic of policy advocacy to close the digital divide (Kuilema 2012 ; Queiro-Tajalli et al 2003 ). At the same time, the US National Association of Social Workers (NASW) has compared broadband access with other vital services and utilities including water and electricity (Pace 2010 ).…”
Section: Digital Access Is a Human Rights And Social Justice Issuementioning
confidence: 99%